THE CHALLENGES OF ISLAMIC TRADE FINANCE IN PROMOTING SMES IN IDB MEMBER COUNTRIES - Abd elrahman Elzahi Saaid Ali (European Scientific Journal, ESJ, 2013)
Accessing financing is one of the most formidable challenges facing Small and Medium Enterprises (SMEs); particularly in the least developing member countries (LDMC) of IDB. Given their low capital base, the availability of financial resources is essential for the SMEs growth. This research attempts to investigate the challenges and limitations facing the use of Islamic finance to promote Small and Medium Enterprises (SMEs) in IDB member countries. Secondary data from member Countries were collected and analyzed to identify the binding constraints in using Islamic finance in promoting SMEs. The findings of this study show- that despite of the recent growth of the Islamic institutions and the development of new Islamic financing products, still there is no favorable environment for Islamic finance to play vital role in the development of SMEs in the IDB member countries. The main reasons might be due to the weakness in the development of trade and the Islamic financing infrastructures. Given the uprising unemployment in many member countries, this study makes specific recommendations to the governments, Islamic banks management as well as IDBG to contribute in removing the challenges associated with accessing the sources of financing to encourage Islamic finance to further promote SMEs